2014
DOI: 10.1371/journal.pone.0090520
|View full text |Cite
|
Sign up to set email alerts
|

Sulforaphane Inhibits Invasion via Activating ERK1/2 Signaling in Human Glioblastoma U87MG and U373MG Cells

Abstract: BackgroundGlioblastoma has highly invasive potential, which might result in poor prognosis and therapeutic failure. Hence, the key we study is to find effective therapies to repress migration and invasion. Sulforaphane (SFN) was demonstrated to inhibit cell growth in a variety of tumors. Here, we will further investigate whether SFN inhibits migration and invasion and find the possible mechanisms in human glioblastoma U87MG and U373MG cells.MethodsFirst, the optimal time and dose of SFN for migration and invas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
46
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 51 publications
5
46
0
Order By: Relevance
“…SFN may suppress cancer progression via a few anti-proliferative mechanisms (12)(13)(14)(15). In a previous study, we found that SFN inhibited invasion in human glioblastoma cells through activation of the ERK1/2 signaling pathway (16). However, whether SFN inhibits invasion in human prostate cancer cells remains to be determined.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations
“…SFN may suppress cancer progression via a few anti-proliferative mechanisms (12)(13)(14)(15). In a previous study, we found that SFN inhibited invasion in human glioblastoma cells through activation of the ERK1/2 signaling pathway (16). However, whether SFN inhibits invasion in human prostate cancer cells remains to be determined.…”
Section: Introductionmentioning
confidence: 90%
“…Previous results demonstrated that human chorionic gonadotropin β (hCGβ) promoted cell migration and invasion in human glioblastoma and prostate cancer cells by increasing the expression and activity of MMP-2, resulting from the sustained activation of ERK1/2 (26,27). It was also found that the sustained phosphorylation of ERK1/2 by SFN contributed to the suppression of migration and invasion in human glioblastoma cells (16). Thus, in the present study, we investigated whether SFN inhibited invasion in human prostate cancer cells via sustained activation of ERK1/2 and the downstream signaling.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…737 In a cell culture model, SFN inhibited glioblastoma cell migration and invasion. 738 SFN (20 µM) reduced the formation of cell pseudopodia by phosphorylating ERK1/2 in a sustained way, contributing to the downregulated MMP-2 (matrix metalloproteinase) expression and activity associated with metastasis.…”
Section: Erk/mapk Signalling Pathway: Day 0 -Daymentioning
confidence: 99%